Science literacy in the Malaysian ESL context - Abdullah, Ain Nadzimah; Chan, Swee Heng; Mazlan, Mazlina (Malaysian Association of Modern Languages, 2013)
English for Science and Technology (EST) was introduced in 2003 as an elective school subject for the learning of scientific content in English, indicative of Malaysia’s realization of the export value of English for international commerce. EST lays the foundation for the use of English in the fields of science and technology as a preparatory course for students intending to extend into tertiary education where science-based courses are taught in English. The theoretical foundation for language learning of this nature lies in the blending of content and its integration into the learning experience. This approach anchors on the assumption that content learning is facilitated through language exposure. In the context of the interest generated for the learning of Science in English, this study was conceptualized to investigate the relevance of EST to the students in terms of their attitudes towards the subject. The study surveyed a total of 212 secondary four public school students in an urban community. Collection of data was through the use of self-reporting scaled questionnaires administered to students in EST classrooms. The findings revealed a hierarchy of preferred topics and these findings were also correlated to topics found in the textbook. There was also a difference in opinion between male and female respondents in topic selection. The responses of the students towards EST relevance for the school curriculum were also moderated. A systematic study of this nature will help to improve and account for English language learning in school and has implications for maintaining education relevance in effective language learning.